2015
DOI: 10.1002/ejsp.2128
|View full text |Cite
|
Sign up to set email alerts
|

Explicit but not implicit sexist beliefs predict benevolent and hostile sexist behavior

Abstract: Much work has been carried out on sexist attitudes, but only little on sexist behaviors. The goal of the present research was to close this gap by testing how a variety of benevolent and hostile sexist behaviors correlate with implicit and explicit sexist attitudes. In Study 1 (N = 126), we developed implicit association tests for benevolent sexism and hostile sexism and illustrated that implicit and explicit benevolent sexist beliefs, as well as implicit and explicit hostile sexist beliefs, were positively co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Social-psychological studies have further shown that TPEs are habitually analyzed according to their demographic composition (e.g., whether those involved in an encounter differ in terms of their race; Pryor, Reeder, & Monroe, 2012) and their momentary level of formality, intimacy, rapport, and subordination/domination (e.g., Burgoon, Buller, Hale, & de Turck, 1984; Mason, Magee, & Fiske, 2014). Additional impressions of importance seem to concern whether TPEs entail positive or negative interpersonal behavior (e.g., kissing vs. pushing someone; Vrticˇka, Sander, & Vuilleumier, 2012), primarily serve a bonding or an instrumental function (e.g., hugging vs. carrying a heavy box; Canessa et al, 2012; Quadflieg, Ul-Haq, & Mavridis, 2016), and/or follow prevalent norms of social conduct (e.g., whether a man or a woman proposes marriage; de Oliveira Laux et al, 2015). Finally, TPEs frequently trigger far-reaching speculations about people’s type of acquaintance and interpersonal obligations (e.g., whether two people are strangers, friends, or family; Costanzo & Archer, 1989).…”
Section: What Are Encounter-based Impressions?mentioning
confidence: 99%
See 2 more Smart Citations
“…Social-psychological studies have further shown that TPEs are habitually analyzed according to their demographic composition (e.g., whether those involved in an encounter differ in terms of their race; Pryor, Reeder, & Monroe, 2012) and their momentary level of formality, intimacy, rapport, and subordination/domination (e.g., Burgoon, Buller, Hale, & de Turck, 1984; Mason, Magee, & Fiske, 2014). Additional impressions of importance seem to concern whether TPEs entail positive or negative interpersonal behavior (e.g., kissing vs. pushing someone; Vrticˇka, Sander, & Vuilleumier, 2012), primarily serve a bonding or an instrumental function (e.g., hugging vs. carrying a heavy box; Canessa et al, 2012; Quadflieg, Ul-Haq, & Mavridis, 2016), and/or follow prevalent norms of social conduct (e.g., whether a man or a woman proposes marriage; de Oliveira Laux et al, 2015). Finally, TPEs frequently trigger far-reaching speculations about people’s type of acquaintance and interpersonal obligations (e.g., whether two people are strangers, friends, or family; Costanzo & Archer, 1989).…”
Section: What Are Encounter-based Impressions?mentioning
confidence: 99%
“…pushing someone;Vrtička, Sander, & Vuilleumier, 2012), primarily serve a bonding or an instrumental function (e.g., hugging vs. carrying a heavy box;Canessa et al, 2012;Quadflieg, Ul-Haq, & Mavridis, 2016), and/or follow prevalent norms of social conduct (e.g., whether a man or a woman proposes marriage; de Oliveira Laux,Ksenofontov, & Becker, 2015). Finally, TPEs frequently trigger far-reaching speculations about people's type of acquaintance and interpersonal obligations (e.g., whether two people are strangers, friends, or family;Costanzo & Archer, 1989).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, women who expected benevolent sexism in the workplace had worse performance and results (Dardenne, Dumont, & Bollier 2007); moreover, those who supported benevolent sexism were more likely to accept a sexist male partner who was apparently protective despite a potential negative impact on their career aspirations (Hammond & Overall 2013;Moya, Glick, Expósito, de Lemus, & Hart 2007). The validation studies of the ASI (Glick & Fiske 1996;Glick et al 2000) have demonstrated that men reported higher levels of hostile sexism than women do; in particular, they showed negative attitudes toward career women and positive attitudes toward housewives because career women deviated from the notion of the ideal of wife and mother (Oliveira Laux, Ksenofontov, & Becker 2015;Rudman 2005). It also emerged that benevolent sexism is more common than hostile sexism, and even if women reject hostile sexism, they tend to accept its benevolent form in line with the system-justification theory (Jost, Burgess, & Mosso 2001;Pacilli, Taurino, Jost, & Van Der Toorn 2011).…”
mentioning
confidence: 99%
“…It highlights specifically that numerous perceiver attributes seem to affect both individual-and encounter-based impressions, including perceivers' age and mental health (see above), but also perceivers' gender, personality, social attitudes, and emotional state (cf. Bernieri and Gillis 1995;Costanzo and Archer 1989;Derlega et al 1989;de Oliveira Laux et al 2015;Forgas 1993Forgas , 1995Hansen and Hansen 1988;Kammrath and Scholer 2011;Katsumi et al 2017). In consequence, the model calls on contemporary researchers to establish which perceiver attributes (if any) affect encounter-based impressions more strongly than individual-based impressions or interact with content or target attributes of encounter-based impressions in a unique manner.…”
Section: The Role Of Perceiver Attributes In Forming Encounter-based mentioning
confidence: 99%